The in situ observation of faceted dendrite growth during the directional solidification of GaSb. (15th July 2019) - Shiga, Keiji; Kawano, Masato; Maeda, Kensaku; Morito, Haruhiko; Fujiwara, Kozo
Abstract: In this work, crystal–melt interfaces were directly observed during the directional solidification of molten GaSb having a stoichiometric composition, and the formation of dendrite structures was studied. With increases in growth velocity, the planar crystal–melt interface became unstable and dendrite growth was initiated. Dendrites having 111 facets were found to grow in either the 〈110〉 or 〈112〉 directions, and a pair of twin boundaries was identified at the center of a dendrite. The results show that the growth of dendrites in GaSb is associated with nucleation at twin-related reentrant corners. Graphical abstract: Unlabelled Image